Assistive technologies for the interaction of the elderly : the development of a communication device for the elderly with complementing illustrations and examples - Moritz, Eckehard Fozzy (Advanced Technologies and Societal Change,, 2014)
This book presents a wealth of insights and new conceptualizations for the development of Assistive Technologies for the Interaction of the Elderly. The book arranges the chapters according to important aspects of maximizing the use value in innovation projects. Every chapter will include an executive summary reporting the main results, a storyline using everyday language, and scientific excursions, wherever useful. The book shows how an innovation project should be structured towards maximum use value and how a project should be structured in order to make a difference. It describes the useful categorization of the large group of the elderly to maximize the focus of the innovation and demonstrates the user involvement into innovation activities. Of course, the assessment of such innovative projects is discussed as well as the "lessons learned". The book also explores the business opportunities and the financial evaluation of aspects of assistive technology.